Governance and Financial Difficulties of Conventional Banks - Sumail, La Ode (Review of Management and Entrepreneurship, 2019)
This study examines the connection between governance, financial performance, and financial difficulties of 27 conventional private banks during the pe3riod of 2015-2018. In order to meet the accuracy of the model in the regression analysis, the Lagrange Multiplier test was previously performed so that the Fixed Effects model was chosen. The relationship of insider ownership with ROA tends to be in the shape of inversed-U and the relationship between institutional ownership and ROA is significantly positive. The relationship between ROA and financial difficulties is significantly negative. Older or established large scale banks tend to have high ROA. This happens because the greater the assets, the healthier the cash flow of the bank, so that the potential for return of asset is quite high and financial difficulties tend to be low or avoidable.